Sex differences in patients undergoing transcatheter aortic valve replacement in Asia. Issue 1 (8th January 2021) - Chiam, Paul T L; Hayashida, Kentaro; Watanabe, Yusuke; Yin, Wei-Hsian; Kao, Hsien-Li; Lee, Michael K Y; Posas, Fabio Enrique; Chandavimol, Mann; Buddhari, Wacin; Dy, Timothy C; Nguyen, Ngoc Quang; Kim, Won Jang; et al.
Abstract : Objectives: Transcatheter aortic valve replacement (TAVR) is increasingly performed. Physically small Asians have smaller aortic root and peripheral vessel anatomy. The influence of gender of Asian patients undergoing TAVR is unknown and may affect outcomes. The aim of this study was to assess sex differences in Asian patients undergoing TAVR. Methods: Patients undergoing TAVR from eight countries were enrolled. In this retrospective analysis, we examined differences in characteristics, 30-day clinical outcomes and 1-year survival between female and male Asian patients. Results: Eight hundred and seventy-three patients (54.4% women) were included. Women were older, smaller and had less coronary artery and lung disease but tended to have higher logistic EuroSCOREs. Smaller prostheses were used more often in women. Major vascular complications occurred more frequently in women (5.5% vs 1.8%, p<0.01); however, 30-day stroke and mortality (women vs men: 1.5% vs 1.6%, p=0.95% and 4.3% vs 3.4%, p=0.48) were similar. Functional status improvement was significant and comparable between the sexes. Conduction disturbance and permanent pacemaker requirements (11.2% vs 9.0%, p=0.52) were also similar as was 1-year survival (women vs men: 85.6% vs 88.2%, p=0.25). The only predictors of 30-day mortality were major vascular injury in women and age in men. Conclusions: Asian women had significantly smaller stature and anatomy with some differences in clinical profiles. Despite more frequent major vascular complications, women had similar 30-day stroke or mortality rates. Functional status improvement was significant and comparable between the sexes. Conduction disturbance and permanent pacemaker requirements were similar as was 1-year survival.